Multi-stakeholder process strengthens agricultural innovations and sustainable livelihoods of farmers in southern Nigeria - Bisseleua, D.H.B.; Idrissou, L.; Olurotimi, P.; Ogunniyi, A.; Mignouna, Djana B.; Bamire, S.A. (Informa UK Limited, 2018)
Purpose: In this paper, we explore the strategic role of Multi-stakeholder processes (MSP) in agricultural innovations and how it has impacted livelihood assets’ (LAs) capital dynamics of stakeholders in platforms in West Africa.